Epidemiological Surveillance, Variability, and Evolution of Isolates Belonging to the Spanish Clone of the 4,[5],12:i:- Monophasic Variant of Salmonella enterica Serovar Typhimurium - Xenia Vázquez; Patricia García; Javier Fernández; Víctor Ladero; Carlos Rodríguez-Lucas; Jürgen J. Heinisch; Rosaura Rodicio; M. Rosario Rodicio (Antibiotics)
Background/Objective: The present study focused on the analysis of the Spanish clone belonging to the successful 4,[5],12:i:- monophasic variant of Salmonella enterica serovar Typhimurium. Methods: All isolates of the clone recovered in a Spanish region from human clinical samples between 2008 and 2018 (N = 14) were investigated using microbiological approaches and genome sequence analysis. In addition, they were compared with isolates from the years 2000 to 2003 (N = 21), which were previously characterized but had not yet been sequenced. Results: Phylogenetic analyses indicate that all isolates are closely related (differing by 1 to 103 SNPs) but belong to two clades termed A and B. With few exceptions, clade A comprised isolates of the first period, also including two “older” control strains, LSP 389/97 and LSP 272/98. Clade B only contained isolates from the second period. Isolates from both periods were resistant to antibiotics and biocides, with almost all resistance genes located on large IncC plasmids, additionally carrying pSLT-derived virulence genes. The number of resistance genes was highly variable, resulting in a total of 22 ABR (antibiotic biocide resistance) profiles. The number of antibiotic resistance genes, but not that of biocide resistance genes, was considerably lower in isolates from the second than from the first period (with averages of 5.5 versus 9.6 genes). Importantly, IS26, which resides in multiple copies within these plasmids, appears to be playing a crucial role in the evolution of resistance, and it was also responsible for the monophasic phenotype, which was associated with four different deletions eliminating the fljAB region. Conclusions: the observed reduction in the number of antibiotic resistance genes could correlate with the loss of adaptive advantage originating from the ban on the use of antibiotics as feed additives implemented in the European Union since 2006, facilitated by the intrinsic instability of the IncC plasmids. Two consecutive IS26 transposition events, which can explain both the clonal relationship of the isolates and their variability, may account for the observed fljAB deletions.